The Effectiveness of Mindfulness-Based Schema Therapy on Self-Focused Attention and Fear of Negative Evaluation in Men with Generalized Anxiety Disorder - Jalili, Soraya; Aleyasin, Seyed Ali (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The aim of the present study was to determine the effectiveness of mindfulness-based schema therapy on self-focused attention and fear of negative evaluation in men with generalized anxiety disorder (GAD).Methods and Materials: This study employed a quasi-experimental research design with a pretest-posttest format including an experimental group and a control group. The statistical population consisted of all men with generalized anxiety disorder in western Tehran. From this population, 30 individuals were selected through convenience sampling and randomly assigned to the experimental (n = 15) and control (n = 15) groups. To measure the research variables, the Demographic Characteristics Questionnaire, the Attention Focus Questionnaire (Woody et al., 1997), and the Fear of Negative Evaluation Scale (Watson & Friend, 1969) were utilized. Data were analyzed using SPSS Version 27 and by conducting descriptive and inferential statistical tests, including multivariate and univariate analysis of covariance (MANCOVA and ANCOVA).Findings: The results revealed that mindfulness-based schema therapy had a statistically significant effect on reducing self-focused attention and fear of negative evaluation in men with generalized anxiety disorder, with a confidence level of 99%.Conclusion: Therefore, it can be concluded that mindfulness-based schema therapy is significantly effective in decreasing self-focused attention and reducing the intensity of fear of negative evaluation in men diagnosed with generalized anxiety disorder. Accordingly, this therapeutic approach can be considered an effective and beneficial intervention for the treatment of GAD.